133k views
13 votes
2y=-x+9
3×-6y=-15 whats the solution to the system​

2 Answers

2 votes

Answer:

Explanation:

2y = -x +9

3x - 6y = -15

The solution is the value of x and y that will make the two equations true in the same time.

3x-6y = -15; divide both sides by 3

x-2y = -5; substitute 2y for -x+9 because the first equation tell us they are equal

x-(-x+9) = -5; open parenthesis

x+x-9 = -5 ; add 9 to both sides and combine like terms

2x = -5 +9; 2x = 4; divide both sides by 2

x= 2

Substitute x for 2

2y = -x+9 ; 2y = -2 +9 ; 2y = 7; y = 7/2 = 3.5

Solution is (2, 3.5)

User Gilad M
by
5.6k points
6 votes

Answer:

(2, 7/2)

General Formulas and Concepts:

Pre-Algebra

Order of Operations: BPEMDAS

  1. Brackets
  2. Parenthesis
  3. Exponents
  4. Multiplication
  5. Division
  6. Addition
  7. Subtraction
  • Left to Right

Equality Properties

  • Multiplication Property of Equality
  • Division Property of Equality
  • Addition Property of Equality
  • Subtract Property of Equality

Algebra I

  • Coordinates (x, y)
  • Terms/Coefficients
  • Solving systems of equations using substitution/elimination

Explanation:

Step 1: Define Systems

2y = -x + 9

3x - 6y = -15

Step 2: Rewrite Systems

2y = -x + 9

  1. [Division Property of Equality] Divide 2 on both sides: y = -x/2 + 9/2

Step 3: Redefine Systems

y = -x/2 + 9/2

3x - 6y = -15

Step 4: Solve for x

  1. Substitute in y: 3x - 6(-x/2 + 9/2) = -15
  2. Distribute -6: 3x + 3x - 27 = -15
  3. Combine like terms: 6x - 27 = -15
  4. [Addition Property of Equality] Add 27 on both sides: 6x = 12
  5. [Division Property of Equality] Divide 6 on both sides: x = 2

Step 5: Solve for y

  1. Define original equation: 2y = -x + 9
  2. Substitute in x: 2y = -2 + 9
  3. Add: 2y = 7
  4. [Division Property of Equality] Divide 2 on both sides: y = 7/2
User Janos
by
5.0k points